Sosialisasi DBD Bentuk Upaya Pencegahan dan Penurunan Kasus Demam Berdarah di Desa Kebonadem - Faila Syifa Al Karim; Miftachul Nurhidayah; Fadhilah Endina Mahirah; Mohammad Yoga Apriyanto; Tafdhila Tsurayya; Dwi Hartanti (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Socialization on the prevention of Dengue Hemorrhagic Fever (DBD) in Kebonadem Village on July 20 2024 aims to increase public awareness about the dangers of DBD and steps to prevent it. The main problem faced is the high risk of dengue fever transmission due to population density and community behavior that does not maintain environmental cleanliness, which supports the breeding of the Aedes aegypti mosquito. The urgency of this outreach is very high considering that dengue fever cases often cause Extraordinary Events (KLB) and the fatal impacts they can have. The results of this outreach show a significant increase in public understanding regarding preventive measures such as the application of 3M Plus (Draining, Covering, Burying and Sprinkling abate powder) as well as the early signs of dengue fever. Active participation in discussions and implementing new habits, such as cleaning water reservoirs, indicates the positive impact of this activity. Despite progress, consistency in implementing prevention habits and ongoing support from various parties is still needed to ensure long-term success. Regular evaluations will help assess the effectiveness of the program and reduce the number of dengue cases in the village, making it an example of success in dengue prevention in other communities.